Medical-Examiner Assessment of Aesthetic Damages (Saúde Ética & Justiça, 2017)
The expert assessment of damage constitutes a technical activity, to which apply the rules of the Medical Art, within the context of the law. The medical report must be comprehensive and allow understanding the actual situation of the individual. The evaluation of the expert should ensure clarification of the judgment, thus contributing to justice. It is fundamental that personal injury is identified, described, and valued according to a rigorous scientific method. This article takes into account the experience of the Institute of Social Medicine and Criminology of the State of São Paulo (IMESC) to discuss Aesthetic Damage, both in its diagnosis and in its assessment within the Brazilian legal framework. The assessment method employed is based on a quantitative-descriptive scale, aiming for harmonization in its consideration, within the general principle of integral reparation of damages, in a contextualized and grounded manner.